Total Prostate-Specific Antigen (tPSA) Outperforms Free PSA Percentage (fPSA%) in Detecting High-grade Prostate Carcinoma (PCa) in Patients Older than 60 Years of Age - Sun, MD, PhD, Tong; Cornejo, MD, Kristine; Al-Turkmani, PhD, M.Rabie; Rao, PhD, Lokinendi V (North American Journal of Medicine and Science, 2019)
The PSA-based prostate cancer (PCa) screening remains a controversial topic. Total PSA (tPSA) levels along with % free PSA (fPSA%) still remain the most widely used screening markers for PCa in clinical practice. To assess tPSA and fPSA% screening performance and threshold to identify high-grade PCa, a large hospital-based cohort study is executed. A total of 853 patients who received 6 or 12 core prostate biopsies between January 2011 and August 2016 were included in the study and the tPSA and fPSA% were evaluated. The highest tPSA and lowest fPSA% levels within the prior 2 years of the biopsies were scrutinized. Both tPSA and fPSA% have the ability to discriminate patients with PCa from men without PCa. Intriguingly, only tPSA levels in patients older than 60 years showed a significant difference between men with and without PCa. More aggressive PCa also tends to occur in older patients (Ptrend = 0.045). With a level of tPSA > 20ng/mL, the likelihood ratio for detecting PCa with pathologic Gleason score > 8 is 6.43, with 95% specificity and 30% sensitivity. fPSA% did not show a correlation with PCa histological grades or patients’ age. Both tPSA and fPSA% have significant predictive values in PCa screening. The tPSA levels with the highest predictive value for PCa were achieved in patients older than 60 years in our cohort. Furthermore, a higher level of tPSA, such as 20 ng/mL rather than the widely adopted screening cutoffs (i.e. 4.0 or 10.0 ng/mL) is significantly associated with a high-grade PCa. [N A J Med Sci. 2019;12(1):007-013. DOI: 10.7156/najms.2019.1201007]